1994
DOI: 10.1152/ajpendo.1994.266.5.e760
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of metallothionein concentrations in rat brain: effect of glucocorticoids, zinc, copper, and endotoxin

Abstract: The effects of known inducers of liver metallothionein (MT) synthesis on MT concentrations in the rat brain have been determined using antibodies that are specific for MT I and II and do not cross-react with MT III. There were substantial differences in the MT concentrations in different areas of the brain. Dexamethasone increased MT levels after 24 h in the frontal cortex, cortex, medulla oblongata plus pons, midbrain, striatum, hippocampus, and cerebellum but not in the hypothalamus. Corticosterone produced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
49
1
1

Year Published

1994
1994
2012
2012

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(55 citation statements)
references
References 24 publications
4
49
1
1
Order By: Relevance
“…In the spinal cord, the mean microglial densities in the mutant white matter Ž . Ž are about threefold 10-12 days and fivefold [20][21][22] . days higher than in normal animals.…”
Section: Introductionmentioning
confidence: 99%
“…In the spinal cord, the mean microglial densities in the mutant white matter Ž . Ž are about threefold 10-12 days and fivefold [20][21][22] . days higher than in normal animals.…”
Section: Introductionmentioning
confidence: 99%
“…The reason for this high diversity of MT isoforms is currently unknown. MT1 and MT2 can be induced in vivo by factors including zinc (5), glucocorticoids (6), cytokines such as IL-6 and TNF␣ (7)(8)(9), and regulatory response elements in their genes (10).…”
mentioning
confidence: 99%
“…Since stress caused by surgery associated with intracerebroventricular (i.c.v.) administration of saline or ether anesthesia was not able to induce MT levels in any of the eight brain areas studied [66], it may be concluded that brain MT is also sensitive to the intensity/length of exposure to the stressor.…”
Section: Acute Stressmentioning
confidence: 79%
“…These results were confirmed and extended in a study from our laboratory, which indicated MT induc tion by zinc (0.44 pmol i.e.v. in the third ven tricle) in some but not all rat brain areas, a process apparently driven by increased zinc uptake [66]. Thus, zinc can induce brain MT levels and, as stated above, restraint stress increases extracellular zinc levels in some brain areas [47], After measuring cytosolic zinc levels in the same brain areas where MT levels have been measured, however, it ap pears that no clear parallelism can be drawn between zinc and MT levels in basal situa tions ( fig.…”
Section: Factors Controlling Brain M T During Stressmentioning
confidence: 95%
See 1 more Smart Citation